Prevalence of childhood asthma and its immediate outcome - At tertiary care rural hospital - Muley, Prasad; Dave, Hemal; Patel, Maitrey; Shah, Unnati; Dosi, Jigar; Mehta, Ankur (Indian Journal of Child Health, 2017)
Introduction: Asthma is a chronic inflammatory disorder of the airways resulting in episodic airway obstruction. Globally, childhood asthma is increasing in the prevalence, despite improvements in investigation and treatment. Childhood asthma seemed more prevalent in urban population and now even in rural areas of India. Objectives: To know the prevalence, assess the risk factors, severity, and immediate outcome of the treatment offered to asthmatic children in a tertiary rural hospital. Materials and Methods: All the diagnosed asthmatic children up to 18 years were enrolled in the study. All the patients of pulmonary Koch’s, congenital heart disease and chronic lung disease were excluded from the study. Clinical profile was noted in recruited patients. Results: The prevalence of childhood asthma among children visiting to our department was 3.93%. 58 (48.33%) had age of onset before the age of 6 years. Asthma was more prevalent in boys. 116 (96.66%) children presented with complain of cough, and 118 (98.33%) children had associated breathlessness. Common precipitating factors were change in season (71.66%), pollen allergy (58.33%), air pollutieon (45.00%), and passive smoking (23.33%). Exercise-induced asthma was seen in 55% cases, diurnal variation in 60% and 28.33% children had family history of atopic disease. Majority of the patient was undernourished. The average duration of stay in persistent asthma is 1.8 times more than in intermittent asthma. Conclusion: Significant number of patient becomes symptomatic before the 6 years of age. Prevention of child from exposure to passive smoking, environmental improvement, and allergen avoidance are major aspects for prevention of asthma exacerbations.